International Monetary Fund Annual Report 1998. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1998)
The Annual Report to the Board of Governors reviews the IMF's activities, policies, and liquidity position during the financial year (May 1, 1997 through April 30, 1998), as well as developments in the world economy, including balance of payments problems of its member countries, exchange rates, international and emerging capital markets, fiscal considerations in policy making, data issues, and the debt situation. the 1998 Report highlights the Asian financial crisis and its repercussions and early lessons for policy, and discusses approaches for strengthening the international monetary system. The 1998 Report also provides information on the IMF's data dissemination standards, the contents of IMF-supported adjustment programs, the IMF- World Bank initiative to assist heavily indebted poor countries, the IMF's role in governance issues, and the status of New Arrangements to Borrow and the Eleventh General Review of Quotas. Appendices include a report on international reserves, details of the IMF's financial operations, major decisions taken by the Executive Board, communiques of the Interim and Development Committees, capital and administrative budgets and information on staffing, the external relations activities, audited financial statements of IMF accounts and facilities, and other information. Published in September.